PENGEMBANGAN SI GEOGRAFIS LOKASI TKA DAN TPA DIBAWAH NAUNGAN BADKO BANTUL BERBASIS ANDROID - Apriliya Kurnianti; Haris Setyawan; Adiatsa Putra Santika; Risang Prakosa (Universitas Muhammadiyah Gresik, 2022)
BADKO (Coordination Agency) TKA-TPA Bantul Regency is an institution that aims to coordinate, foster, and improve the quality of the management of TKA-TPA in Bantul Regency. The management of TKA-TPA in Bantul Regency is currently using a web-based information system but still requires evaluation to improve its management. Some problems that exist in the field, among others, in the data collection process, the BADKO TKA-TPA Management often encounter obstacles, among others; access to information regarding data collection is often late, admin's knowledge of the use of information systems is still very limited, network connections are sometimes a problem when filling in data using a PC or laptop, and information systems that are considered less user friendly for users. The BADKO information system has previously been developed in the first and second years of service based on a website and webview. Development up to the webview level is still lacking, because it still won't be able to match the Android-based system. This third year of service, will focus on developing mobile app information systems using the android platform. The consideration of developing applications from the web to android is because almost all admins under BADKO use android smartphones